2022
DOI: 10.3390/ijms23116121
|View full text |Cite
|
Sign up to set email alerts
|

Energy Deposition around Swift Carbon-Ion Tracks in Liquid Water

Abstract: Energetic carbon ions are promising projectiles used for cancer radiotherapy. A thorough knowledge of how the energy of these ions is deposited in biological media (mainly composed of liquid water) is required. This can be attained by means of detailed computer simulations, both macroscopically (relevant for appropriately delivering the dose) and at the nanoscale (important for determining the inflicted radiobiological damage). The energy lost per unit path length (i.e., the so-called stopping power) of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 147 publications
0
12
0
Order By: Relevance
“…However, both the inelastic and the elastic cross sections models become inaccurate for low energies, thus increasing the results uncertainty. In the future, the Rutherford model can be replaced with the partial wave expansion to improve the elastic scattering collisions, in fact recent studies showed the importance of elastic scattering models and their effect on numerical simulations [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, both the inelastic and the elastic cross sections models become inaccurate for low energies, thus increasing the results uncertainty. In the future, the Rutherford model can be replaced with the partial wave expansion to improve the elastic scattering collisions, in fact recent studies showed the importance of elastic scattering models and their effect on numerical simulations [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The positions of all DNA and water atoms are held constant, as the time scales for these simulations (0.27–3.38 fs, depending on projectile ion velocity) are too short for any notable nuclear motion . The projectile ion is moved at a constant velocity of interest for obtaining the velocity-dependent electronic stopping power curve. , The electronic stopping power, or the energy transfer rate from the projectile ion to target, is a crucial property for many applications, including beam cancer therapy. As the projectile ion travels through the simulation cell, the electron density changes in response to the time-dependent potential generated by the projectile ion until the ion reaches the end of its trajectory, and the simulation is stopped. By moving the projectile at a constant velocity, while all other atoms are held in place, the total energy of the nonequilibrium simulation is not conserved, as work is done throughout by the projectile ion. ,, Therefore, changes in the total energy of the system can be used to calculate the electronic stopping power as a function of the projectile ion velocity (see Figures S4 and S5 for details) …”
Section: Computational Methodsmentioning
confidence: 99%
“…22 Additionally, the water-ions generated by the interaction processes cause an additive charged background that polarizes the neutral water molecules within the ion track. There is no detailed study about proton tracks in liquid water regarding free charge concentrations, but similar studies about carbon-tracks in liquid water, 23 ion tracks in various solids 24 and models like the thermal spike model for protons in liquid water 25 suggest that this charge background is present as long as the radical dissipation time of ≈ 10 ps. Therefore, an electron ionized in the ion track could not encounter a neutral water background in its vicinity, showing an energy structure as in seen figure 1, but rather a highly polarised medium.…”
Section: Electron Solvation Modelmentioning
confidence: 99%